Direct endothelial ENaC activation mitigates vasculopathy induced by SARS-CoV2 spike protein - Romero, Maritza J.; Yue, Qian; Singla, Bhupesh; Hamacher, Jürg; Sridhar, Supriya; Moseley, Auriel S.; Song, Chang; Mraheil, Mobarak A.; Fischer, Bernhard; Zeitlinger, Markus; Chakraborty, Trinad; Fulton, David; et al. (Frontiers in Immunology, 2023)
Although both COVID-19 and non-COVID-19 ARDS can be accompanied by significantly increased levels of circulating cytokines, the former significantly differs from the latter by its higher vasculopathy, characterized by increased oxidative stress and coagulopathy in lung capillaries. This points towards the existence of SARS-CoV2-specific factors and mechanisms that can sensitize the endothelium towards becoming dysfunctional. Although the virus is rarely detected within endothelial cells or in the circulation, the S1 subunit of its spike protein, which contains the receptor binding domain (RBD) for human ACE2, can be detected in plasma from COVID-19 patients and its levels correlate with disease severity. We show that SARS-CoV2 RBD impairs endothelial ENaC activity, reduces surface hACE2 expression and increases reactive oxygen species (ROS) and tissue factor (TF) generation in monolayers of human lung microvascular endothelial cells (HL-MVEC), as such promoting barrier dysfunction and coagulopathy. The TNF-derived TIP peptide (a.k.a. solnatide, AP301) -which directly activates ENaC upon binding to its a subunit-can override RBD-induced impairment of ENaC function and hACE2 expression, mitigates ROS and TF generation and restores barrier function in HL-MVEC monolayers. In correlation with the increased mortality observed in This is a provisional file, not the final typeset article COVID-19 patients co-infected with S. pneumoniae, as compared to subjects solely infected with SARS-CoV2, we observe that prior intraperitoneal RBD treatment in transgenic mice globally expressing human ACE2 significantly increases fibrin deposition and capillary leak upon intratracheal instillation of S. pneumoniae and that this is significantly reduced by TIP peptide treatment. In conclusion, our data indicate that direct activation of endothelial ENaC should be further evaluated as a novel therapeutic strategy to mitigate COVID-19-associated vasculopathy.